PROFITABILITY IS NOT A CONSIDERATION FOR INVESTORS IN INDONESIAN BANKING SHARES - Isman (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2024)
Objective – This research aims to analyze the effect of profitability on share prices. Design/Methodology/Approach – Sample is a go bank public on the Indonesian Stock Exchange. The type of data used is quantitative data. Quantitative data in the form of stock price data, earnings per share, return on assets, and return on equity. The data source for this research is secondary data from bank financial reports for 2018-2021 from the Indonesian Stock Exchange. The sample in this research was 26 banks that fell into the purpose sampling category. The method used in this research is multiple linear regression analysis with SPSS version 26 software. Findings – The results of this research analysis show that profitability as measured using ROA and ROE does not have a significant effect on share prices. Likewise, it was concluded that EPS had no significant effect on share prices. However, together ROA, ROE and EPS have a significant influence on share prices. Conclusion and Implications – In the 2018-2021 period, Indonesian banking share prices are not determined by movements in earnings per share, return on equity and return on assets due to the impact of the Covid-19 pandemic, which means the majority of investors tend to wait for the pandemic to end to make investment decisions.